When The Tide Recedes: a photographic sojourn along the Singapore River. - Cheah, Lilian. (2008)
This report has been compiled to show why we have chosen Singapore River as the subject or theme of our project, an overview of the pre-production and production process, to explainthe decisions for the images selected and manner of presentation, and to reflect and evaluate the lessons - both good and bad - learnt from the course of working on this project.